Dynamic Characteristics Analysis of the Hub Direct Drive-Air Suspension System from Vertical and Longitudinal Directions - Zhongxing Li; Xinyan Song; Xin Chen; Hongtao Xue (Shock and Vibration)
Hub direct-drive electric vehicles are driving with hub motors, which cause negative vibration directly on wheels and suspensions. To better analyze the problems of dynamic deterioration resulted by coupling excitations from random road and unbalanced magnetic pull (UMP), a cooperative hub direct drive-air suspension (HDD-AS) system is developed, and evaluation indices based on vertical and longitudinal dynamic coupling mechanism are proposed. The vertical and longitudinal characteristics in the time domain under different damping coefficients and motor speeds are demonstrated, and comparison between traditional electric wheel and suspension-integrating models and HDD-AS system model is conducted. Then, the responses of random road excitation and UMP are analyzed, and explanations of vertical and longitudinal characteristics in the frequency domain under different damping coefficients are given. These results provide important insights into the influence of coupling excitations and damping coefficient on the HDD-AS system model. Finally, the effectiveness of the proposed model is verified by the experiment on the test bench.